ПОСАДОВО0ФУНКЦІОНАЛЬНИЙ МЕТОД ТА ГІПОТЕЗА “КОМАНДИРІВ МИРНОГО ЧАСУ” ЯК ІНСТРУМЕНТИ ВИВЧЕННЯ ВІЙСЬКОВОЇ ЕЛІТИ (Zaporizhzhia Historical Review, 2021)
In the article the history of creation of hypothesis of “commanders of peacetime” of imperial direction of the post-Soviet historiography of Second World War has been considoreds, key positions of this hypothesis and the post-functional method closely associated with it have been set up and discovered.